A Study on the Language Network from a Business Development Perspective The Language Network - Patel, Musafa (ATLAS SkillTech University, 2024)
My i n t e r n s h i p e x p e r i e n c e a t T h e L a n g u a g e N e t w o r k , a n i n n o v a t i v e p l a ye r i n t h e E d T e c h s e c t o r s p e c i a l i z i n g i n o n l i n e f o r e i g n l a n g u a g e c o u r s e s , h a s b e e n a r e w a r d i n g j o u r n e y f i l l e d wi t h s i g n i f i c a n t i n s i g h t s a n d p e r s o n a l g r o wt h . D u r i n g t h i s p e r i o d , I h a d t h e p r i v i l e g e o f wo r k i n g a s a S a l e s I n t e r n , e n g a g i n g i n a r o l e t h a t e n t a i l e d d yn am i c r e s p o n s i b i l i t i e s a n d m e a n i n g f u l i n t e r a c t i o n s .
Project Report on A Study on the Language Network from a Business Development Perspective The Language Network (2022-24) Under the Guidance of Prof. Chetana Asbe
Keywords: EdTech; HUMANITIES and RELIGION::Languages and linguistics; Language Networks